EVALUASI PENGGUNAAN OBAT ANTIDIABETIK ORAL PADA PASIEN DIABETES MELITUS TIPE 2 MENGGUNAKAN METODE ATC/DDD DAN DU 90% - Nurshalati Tahar; Alifia Putri Febriyanti; Munifah Wahyuddin; Syahifah Auliyah Hasti (Universitas Islam Negeri Alauddin Makassar, 2020)
Diabetes mellitus is a chronic metabolic disease caused by the pancreas not producing enough insulin or not being able to use the required insulin effectively. Evaluate the use of oral antidiabetic drugs using ATC Diabetes mellitus is a chronic metabolic disease caused by the pancreas not producing enough insulin or not being able to use the required insulin effectively. Evaluate the use of oral antidiabetic drugs using ATC / DDD and DU 90% methods. Oral antidiabetic used in Makassar Hospita Hospital there are 3 types of metformin as many as 1020 units with a dose per unit that is 500 mg with a total use of 601000 mg 99.56%, more than 48 units with a perunit dose of 60 mg with a total dose of 2520 mg 0 , 41%, the last is 41 units of glimepiride with a perunit dose of 2 mg with a total use of 82 0.01%. Of the 3 types of oral antidiabetic, 3 usage patterns were obtained, namely 84% single metformin, 9% metformin + gliclazide combination pattern and 7% metformin + glimepirid combination. Included in the 90% DU segment or included in the list of incoming drugs is collected 90% of drug use after being sorted from the highest and highest percentage of drug use for compilation and low use is the use of metformin, using the correct use of drugs according to the choice, right dose, right delivery time, exact route and right information.